NETWORK OF P- PATH MINIMUM CONSTRAINED CONNECTIVITY FROM CITIES TO HEAD QUARTER (International Journal of Engineering and Computer Science, 2013)
Many Combinatorial programming problems are NP-hard (Non Linear Polynomial), and we consider one of them called Ppath minimum distance connectivity from head quarter to the cities. Let there be n cities and the distance matrix D (i, j, k) is given from ith city to jth city using kth facility. There can be an individual factor which influences the distances/cost and that factor is represented as a facility k. We consider m